Effect sf alien cytoplasm on expression of heterosis and productivity of Indiana mustard (Brassica juncea ) hybrids - KATIYAR, R K; CHAMOLA, R; YADAV, MAMATA (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2004-05 to study the effect of alien (Moricandia amensis( L). DC.) cytoplasm on the expression of heterosis for seed yield and its impact on the productivity of 5 hybrids of Indian mustard (Brassica jurzcea (L.) Czernj. & Coss.). The heterosis declined significantly with replacement of I parent (combiner) with alloplasmic background. The average loss of heterosis which was found to be 6.7% in ’alloplasmic’ x ’euplasmic’ hybrids rose to 26.9% in ’alloplasmic x alloplasmic’ hybrids. ’Pusa Jai Kisan’ x ’RLM 198’ hybrid manifested maximum heterosis (30.0 - 32.2%) for the seed yield with euplasmic parents but the trend of yield loss with the replacement of alloplasmic parents was similar to that of the other hybrids. The detrimental effect of alien cytoplasm of parents on the productivity of hybrids was also noticed. The average seed yield/plot. 2.52 kg of ’euplasmic x euplasmic’ parental hybrids reduced to 2.38 kg with ’alloplasmic’ x ’euplasmic’ and drastically reduced to 1.96 of ’alloplasmic’ x ’alioplasmic’ parental hybrids. The average loss of seed yield in hybrids found to be 5.5 % with one alloplasmic parent rose to a considerable high limit of 22.0% with the use of both alloplasmic parents